Mechanism Design-Based Mathematical Modeling of the Decoy Effect in Housing Type Selection - Sentot Eko Baskoro; I Nyoman Sutapa; Suhartono Suhartono (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2025)
This study develops a mechanism design-based mathematical model to induce a decoy effect in housing selection, shifting consumer preferences from small to large house types. Using an area-per-price utility function and dominance constraints, two optimal decoy configurations (adjacent and strong) are derived analytically. We consider a developer offering a small house (500,000,000 IDR; 40 m2 building; 100 m2 land) and a large house (1,000,000,000 IDR; 100 m2 building; 200 m2 land), and design an additional decoy alternative. By imposing dominance and feasibility constraints, we derive closed-form conditions on the decoy's building area Ad and land area Ld for two price levels, 750,000,000 IDR and 850,000,000 IDR. The resulting adjacent ( = 0.002) and strong ( = 0.010) decoys ensure that the large house weakly dominates the decoy while maintaining internal consistency of preferences. Sensitivity analysis shows that the advantage margin increases linearly with proximity and context intensity parameters. The proposed framework provides developers with an operational and auditable mechanism for housing portfolio design.